Burkholderia pseudomallei antibodies in children, Cambodia. - Wuthiekanun, V; Pheaktra, N; Putchhat, H; Sin, L; Sen, B; Kumar, V; Langla, S; Peacock, S; Day, N (2008)
Antibodies to Burkholderia pseudomallei were detected in 16% of children in Siem Reap, Cambodia. This organism was isolated from 30% of rice paddies in the surrounding vicinity. Despite the lack of reported indigenous cases, melioidosis is likely to occur in Cambodia.